2004
DOI: 10.1108/00400910410518188
|View full text |Cite
|
Sign up to set email alerts
|

What is “enterprise education”? An analysis of the objectives and methods of enterprise education programmes in four European countries

Abstract: This paper explores what constitutes “enterprise education” in four European countries. It proposes a conceptual schema for capturing the various objectives of enterprise education programmes and initiatives. This conceptual schema is then used to categorise the objectives of 50 enterprise programmes from Austria, Finland, Ireland, and the UK. The paper reviews the teaching/learning methods used in these programmes. It discusses what factors are associated with “effective” enterprise education, illustrating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
345
0
19

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 402 publications
(367 citation statements)
references
References 20 publications
3
345
0
19
Order By: Relevance
“…These faculty members need to be equipped to deliver courses, which are often less lecture driven, less theoretical and require a level of entrepreneurial behaviour. Research by Hytti and O'Gorman (2004) in a comparative study of entrepreneurship courses across a number of countries (Ireland being one), found that the trainers lacked the skills and information required about entrepreneurship to provide students with the necessary skills and knowledge for entrepreneurship education. They recommended the need for in-career training to support and address the needs of the trainers to ensure they are better equipped.…”
Section: Teaching Focusmentioning
confidence: 99%
See 1 more Smart Citation
“…These faculty members need to be equipped to deliver courses, which are often less lecture driven, less theoretical and require a level of entrepreneurial behaviour. Research by Hytti and O'Gorman (2004) in a comparative study of entrepreneurship courses across a number of countries (Ireland being one), found that the trainers lacked the skills and information required about entrepreneurship to provide students with the necessary skills and knowledge for entrepreneurship education. They recommended the need for in-career training to support and address the needs of the trainers to ensure they are better equipped.…”
Section: Teaching Focusmentioning
confidence: 99%
“…Galloway and Brown (2002) also suggested that a "cross disciplinary approach" to enterprise education could influence a range of industry sectors including the arts, science and technology disciplines. Furthermore, Hytti and O'Gorman (2004) found that the more successful courses were those which integrated learning across the general educational experience and which introduced enterprise education into other courses. The innate abilities of an individual, coupled with the overall socio-economic environment (ease of establishing a new business, access to finance and advice as well as the prevailing cultural attitudes to entrepreneurship) are extremely important factors in determining whether they pursue an entrepreneurial path.…”
Section: Entrepreneurship Education -Responding To the Needs Of The Imentioning
confidence: 99%
“…Finland is exceptional, generally entrepreneurship education and training in schools internationally has received low ratings every year since expert surveys commenced in 2000 (Martinez et al, 2010) reflecting its priority in national educational policies. Hytti and O'Gorman (2004) reviewed 50 enterprise education programmes over four countries. They argued that the definition of enterprise education was less important than the understanding of enterprise as a subject that encompasses elements of business and entrepreneurship but which requires training of specialist staff.…”
Section: Policy Literaturementioning
confidence: 99%
“…Hytti and O'Gorman (2004) examined 50 educational institutions at different levels in Austria, Ireland and the United Kingdom and concluded that they used the following methods, respectively, according to their frequency of use in entrepreneurship education: Traditional teaching methods, business simulations and workshop studies, guidance, setting up a new business, study visits, games, and competitions and applied teaching.…”
Section: Conclusion Discussion and Suggestionsmentioning
confidence: 99%